(untitled) - Gharajedaghi, Jamshid (Amsterdam, 2006)
An excellent addition to books written on Systems Thinking. It is practical and timely and can be used by a vast majority of professionals such as engineers, planners and managers. I recommend it very highly to practitioners and academics. C. J. Khisty, Dept. of Civil Engineering, Illinois Institute of Technology
Keywords: System analysis,Chaotic behavior in systems,Industrial management,Technological complexity,Quản lý công nghiệp,Hành xử hỗn loạn,Phân tích hệ thống,Phức tạp kỹ thuật